AI in business management : bridging the gap between technology and strategy - Pandey, Jay Kumar, 1987-; Rai, Mritunjay, 1985-; Ray, Samrat, 1980- (Routledge/Productivity Press, 2026)
The book makes AI accessible to business leaders, managers, and decision-makers, providing applied knowledge of how technological capabilities might be matched with corporate strategy.